Decision Model for Saving Stocks Based on TPB and Financial Literacy - Mulyono, Kemal Budi (Fakultas Ekonomi, Universitas Negeri Semarang, 2021)
This study investigated the behavior of investment decisions that were not only assumed on rationality but were also affected by other factors, such as psychological factors, one of which was financial literacy. There were so many causal studies of financial literacy and investment intentions. However, there were still issues of inclusion between studies. Therefore, this study adopted a theory of planned behavior, proposed as an explanatory model for investment intentions associated with financial literacy. By proposing attitude, subjective norms, and perceived behavioral control related to investment as a mediator of investment intention, the unit of analysis was students who were members of the capital market study group spreading across universities in Semarang. The sample used was 170 students conducted through a questionnaire survey, then analyzed descriptive statistics and SEM with the PLST Warp. The results showed that all variables, both attitudes, subjective norms, perceptions of behavioral control, significantly mediated the effect of financial literacy on investment intention in partial mediation. For future research, you can explore the variables of financial education as early predictors associated with this research model to get a holistic picture related to the effectiveness of student financial education.